Effects of an Acute Bout of Exercise on Salivary Lactoferrin Responses among Smokers and Non-Smokers - Ahmad, Halimatun Saadiah; Muhamad, Ayu Suzailiana (Journal of Science and Technology, 2021)
Smoking can weaken immune function as reported in previous studies. However, benefits of exercise in reducing negative effects of smoking on salivary lactoferrin responses is scarce to date. Hence, the purpose of this study is to determine the effects of an acute bout of exercise on salivary lactoferrin responses among smokers and non-smokers. Eighteen sedentary men were recruited; nine smokers (age = 22.4 ± 1.4 years; BMI = 22.1 ± 1.1 kg/m2) and nine non-smokers (age = 22.1 ± 0.7 years old; BMI = 22.5 ± 1.9 kg/m2). In this study, participants cycled at an intensity of 60% maximum heart rate for 60 minutes. Participants were given cool water as much as 3 ml/kg body weight at minutes 20 and 40 during the exercise session. Participants’ body weight and saliva samples were collected at pre and post-exercise. Heart rate and rate of perceived exertion (RPE) were recorded at pre, during and post-exercise. Mixed ANOVA was used to measure significant differences between groups and within group. The results showed that saliva flow rate, lactoferrin concentration and lactoferrin secretion rate were not significantly different (p>0.05) between smokers and non-smokers groups and also between pre and post-exercise within each group. Heart rate and RPE showed significant increased (p